Vascular Pathophysiology in Hearing Disorders - Trune, Dennis R.; Nguyen-Huynh, Anh (Seminars in Hearing, 2012)
The inner ear vasculature is responsible for maintenance of the blood-labyrinth barrier, transport of systemic hormones for ion homeostasis, and supplying nutrients for metabolic functions. Unfortunately, these blood vessels also expose the ear to circulating inflammatory factors resulting from systemic diseases. Thus, although the inner ear blood vessels are critical for normal function, they also facilitate pathological mechanisms that result in hearing and vestibular dysfunction. Despite these numerous critical roles of inner ear vasculature, little is known of its normal homeostatic functions and how these are compromised in disease. The objective of this review is to discuss the current concepts of vascular biology, how blood vessels naturally respond to circulating inflammatory factors, and how such mechanisms of vascular pathophysiology may cause hearing loss.
Keywords: blood-labyrinth barrier; blood vessels; glycocalyx; immunopathology; hearing loss